Exploring possibility of utilizing native arbuscular mycorrhizal fungi for improving phosphorus nutrition in transplanted rice (Oryza sativa L.) of plateau region - and R.K. SINGH, D. MAITI*, M.K. BARNWAL (Indian Phytopathology, 2008)
Possibilities were explored to enhance phosphorus (P) acquisition efficiency of transplanted rice grown under drought prone, shallow rainfed medium land ecosystem by enhancing native arbuscular mycorrhizal (AM) association. Rice seedlings were raised in dry seed beds, previously grown with fodder crops, susceptible to colonization by AM fungi. Out of five different test fodder crops, finger millet (Elusine indica) and little millet (Panicum miliare) induced highest colonization in rice seedlings followed by maize (Zea mays) and sorghum (Sorghum bicolor) leading to higher P acquisition, dry matter production and grain yield at maturity in the same order.